2011
DOI: 10.1136/heartjnl-2011-301156.17
|View full text |Cite
|
Sign up to set email alerts
|

17 Cannabidiol as an anti-arrhythmic, the role of the CB1 receptors

Abstract: Cannabidiol (CBD) has been shown to be anti-arrhythmic (Walsh et al, 2010) and tissue sparing (Durst et al, 2007) in an in vivo rat model of coronary artery occlusion (CAO), although the receptors through which this occurs have yet to be identified. This study was designed to investigate whether the antiarrhythmic effects of CBD are modified by co-administration with a CB1 receptor antagonist (AM251). Experimental CAO was induced by ligation of the LAD coronary artery for 30 min; in sodium pentobarbitone anaes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…CB 1 antagonists were able to lower blood pressure better in the hypertensive rats than the normotensive rats. This may be due to the upregulation of CB 1 receptors in heart and aortic endothelium in hypertensive rats, but not the normotensive cohort [73].…”
Section: Veterinary Ecs: Our Current State Of Knowledgementioning
confidence: 99%
“…CB 1 antagonists were able to lower blood pressure better in the hypertensive rats than the normotensive rats. This may be due to the upregulation of CB 1 receptors in heart and aortic endothelium in hypertensive rats, but not the normotensive cohort [73].…”
Section: Veterinary Ecs: Our Current State Of Knowledgementioning
confidence: 99%
“…11 In their following studies, the same researchers reveal that the antiarrhythmic effect of CBD may not be mediated through the CBD 1 receptor activation during the ischemia. 39 In the present study, although CBD alone suppressed I/Rinduced ventricular arrhythmias, it was not found to be effective against I/R-induced arrhythmias in the presence of adenosine A 1 receptor blockage with DPCPX. These results reveal that the antiarrhythmic effect of CBD may be mediated through the adenosine A 1 receptor activation.…”
Section: Discussionmentioning
confidence: 52%
“…11 In their following studies, the same researchers reveal that the antiarrhythmic effect of CBD may not be mediated through the CBD 1 receptor activation during the ischemia. 39…”
Section: Discussionmentioning
confidence: 99%
“…Hepburn ve ark. (14) anestezi altındaki sıçanlarda bir seçici KB 1 reseptör antagonisti AM251'in miyokardiyal iskemi ile uyarılan ventriküler aritmileri azalttığını göstermiştir. Andrag ve Curtis (15) ise izole sıçan kalbinde AM251'in ventriküler fibrilasyon sıklığını akut iskeminin geç döneminde artırdığı göstermiştir.…”
unclassified
“…Çalışmamızda AM251 ve AM630'un, I/R ile uyarılan ventriküler aritmiler üzerine etkisi ilk kez araştırılmıştır. (17,18), uygulanan dozları ve veriliş zamanı için benzer çalışmalar temel alındı (14,16). AM251 ve AM630 (Sigma Chemical Co.; St. Louis, MO, ABD)1mg/kg/ml dozda intravenöz yolla ligasyondan 10 dakika önce bolus olarak verildi.…”
unclassified